The relationship of prenatal self-care behaviors with stress, anxiety and depression in women at risk of preterm delivery - Seyedeh Mahboobeh Rezaeian; Zahra Abedian; Robab Latifnejad Roudsari; Seyed Reza Mazloom; Salmeh Dadgar (Mashhad University of Medical Sciences, 2017)
Introduction: Pregnancy is associated with extensive mental and physical changes in pregnant women. Stress, anxiety and depression are factors affecting pregnant women's performance that lead to lack of attention to their own self-care. Orem's self-care theory is one of the most widely used theories in the field of self-care. This study was performed with aim to investigate the relationship of self-care behaviors in pregnancy based on Orem's theory with stress, anxiety and depression in women at risk of preterm delivery. Methods: This descriptive correlational study was done on 176 pregnant women in 24-26 week of pregnancy at risk for preterm delivery referring to health centers affiliated to Mashhad University of Medical Sciences in 2015. The research tools included Holbrook risk-scoring for preterm labor questionnaire, demographic and obstetric questionnaire, Hart prenatal care actions scale and DASS21 (stress, anxiety and depression questionnaire). According to Holbrook risk-scoring for preterm labor questionnaire, the subjects who met inclusion criteria were selected. Self-care behaviors were assessed according to Hart prenatal care actions scale, and stress, anxiety and depression were evaluated according to DASS21 questionnaire. Data were analyzed using SPSS software (version16) and using Pearson and Spearman correlation tests. PResults: There was inverse linear significant relationship between prenatal self-care and stress (P =0.004) and depression (P =0.032). But no significant relationship was seen between prenatal self-care and anxiety (P =0.374). Conclusion: The increasing stress and depression in women at risk of preterm delivery reduce self-care behaviors in these patients. Therefore, management and identifying of pregnant women at risk for stress and depression and planning for reducing their stress and depression will lead to increased self-care behaviors in women at risk for preterm delivery.